ISOLASI SENYAWA AKTIF DAN UJI AKTIVITAS EKSTRAK JAHE MERAH (ZINGIBER OFFICINALE) SEBAGAI IMUNOMODULATOR - Masniah, Masniah; Rezi, Jafril; Faisal, Ahmad Purnawarman (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2021)
Red ginger (Zingiber officinale) contains many chemical compounds that have many activities. This study aims to determine the active compounds of Zingiber officinale and immunomodulatory activity that can increase the phagocytosis of macrophage cells and lymphocyte cell proliferation. Red ginger extract compounds were identified using GC-MS. The parameters of immunostimulatory activity were macrophage phagocytosis and lymphocyte proliferation, the preparations were made in several extract concentrations. This research is an experimental study in the laboratory. The research included fresh red ginger, made into ethanol extract, dried. The results were made a suspension, the extract was then given to macrophage cells (phagocytosis testing) and lymphocyte cells (proliferation testing) in vitro to test the immunomodulatory effect. The results showed that the most active extract in macrophage phagocytosis activity was the extract concentration of 500 ppm. While the activity of lymphocyte proliferation was shown by the concentration of group A (Cell, 500 ppm extract, MK, Engerik). The active compound contained in the ethanol extract of red ginger is thought to be Geraniol